Social protection and the challenges of the European Welfare State - Noikokyrakis, Georgios; Sarafis, Pavlos (My University, 2018)
The welfare state as an ideological concept flourished in Europe alongside the remarkable economic growth that took place after the Second World War. Over the next few decades, due partly to the economic turmoil caused by two world oil crises, the welfare state met with criticism and controversy because of its perceived failures and weaknesses (for example failure to eliminate poverty and social exclusion). Currently, several of its support functions are being closely assessed, including health care protection, social welfare characteristics and social security. To this end, the typology and funding sources and the viability of the welfare state are being analyzed, and the various different recipients of the social services of arrangements are under examination. The welfare state and social policy of the European Union 15 (EU-15) countries is classified into four categories depending on the involvement and inter vention of the state in addressing risks and needs. These categories are the social democratic, the conservative-corporative, the liberal and the Southern European model. Each country shapes its own way of involving the state in the financing and delivery of health services. The socio-economic, technological and demographic changes that are taking place in Greece, and more widely in the EU, are constantly changing the environment in which health care is provided. The resultant challenges, along with the global economic crisis, have a serious effect on the welfare state and threaten social cohesion. The current financial crisis in Greece is an unusual situation that is changing peoples’ ideas, perceptions, and the way they think and find solutions. A new era is coming, and the future changes in the welfare state are difficult to predict. Efforts at the national level should be reinforced by a large scale collective reaction, in order for a more substantive global framework of social provision to be established, and to avoid global socio-political competition.
Keywords: European welfare state; Financing; Healthcare systems; Typologies